Posible expansión de la especie exótica Hydroides elegans (Haswell 1883) en zonas portuarias, lagunas costeras contaminadas y otras áreas Costeras con Influencia Antropogénica directa, en el Caribe Colombiano - Tobón Monsalve, Diomer (Revista Urabá Académica, 2022)
In 1979 the serpulid Hydroides elegans was reported for the Colombian Caribbean though this species had already been reported there in the 1950s. However, this species has not been included in the most recent lists of exotic or invasive marine species in Colombia. This species is widely distributed worldwide because it is tolerant to contaminated are as such as ports or coastal lagoons. H. elegans is a fouling species on the hulls of boats and this is the main vector for introduction of the species, making possible its spreading in tropical and subtropical areas. This polychaete should be included in the list of marine and coastal exotic species of the Colombian Caribbean. In addition, the vectors of introduction, the deterioration of the habitat and the specific characteristics of the species, suggest that H. elegans could be expanding in the Colombian Caribbean and, therefore, could potentially be an invasive species.